Hypolipidaemic and anti‐oxidative potential of encapsulated herb (Terminalia arjuna) added vanilla chocolate milk in high cholesterol fed rats. (18th May 2015) - Sawale, Pravin Digambar; Pothuraju, Ramesh; Abdul Hussain, Shaik; Kumar, Anuj; Kapila, Suman; Patil, Girdhari Ramdas
Abstract: BACKGROUND: Atherosclerosis is associated with coronary artery disease and occurs in developing as well as developed countries. In the present investigation, hypolipidaemic and anti‐oxidative properties of encapsulated herb ( Terminalia arjuna, 1.8%) added vanilla chocolate dairy drink was evaluated in high cholesterol fed Wistar rats for 60 days. RESULTS: At the end of the experimental period, a significant decrease in the body weight gain by rats receiving the encapsulated herb extract was noted as compared to high cholesterol fed rats. Administration of microencapsulated herb showed a statistically significant decrease in organ weights (epididymal fat and liver). Moreover, a significant decrease in serum lipids such as triglycerides, total cholesterol, low‐density lipoprotein cholesterol, very‐low‐density lipoprotein cholesterol and atherogenic index was observed with encapsulated Terminalia arjuna extract in high cholesterol fed group. Increases in reduced glutathione and decreases in TBARS levels were also reported in both liver and red blood cell lysates with encapsulated herb supplementation. CONCLUSION: The results demonstrated that the bioactive components (phytosterols, flavanoids, saponins and tannins etc.) which are present in the encapsulated T. arjuna not only withstand the processing conditions but also are effectively released in the intestine and show their effects, such as hypolipidaemic and antioxidant activities, for better treating cardiovascular disease. © 2015 Society of Chemical Industry